Acute Peritonitis and Nonspecific Resistance Factors in the Administration of Ozonized Perfluorane (Experimental Study) - A. M. Golubev; R. M. Ragimov; Z. Sh. Manasova; M. Z. Saidov (Общая реаниматология, 2008)
Objective: to study the effect of ozonized perfluorane on the natural course of acute of fecal peritonitis and congenital (nonspecific) immunity factors during its intraperitoneal administration. Materials and methods. Perfluorane and saline solution were ozonized bubbling with a mixture of ozone and oxygen at a rate of 0.5 l/min and at a preset ozone concentration of 3000 flg/l on a Medozons — BM AOT — H-01-Arz-91 ozonator (OAO «Arzamasskiy Priborostroitelnyi Zavod») for 15 minutes. The concentration of ozone was measured in the solutions on a NF 254/1 spectrophotometer. Experiments were carried out on 200 non-inbred albino male rats in 4 series of experiments. After simulating fecal peritonitis by the procedure developed by S. S. Remennik, the animals were intraperitoneally injected ozonized perfluorane (Series 1), ozonized saline solution (Series 2), perfluorane (Series 3), and saline solution (Series 4) on the basis of 1.5 ml per 100 g of weight. Nine intact rats were used as a control. Results. The congenital immunity parameters (phagocytic block, intracellular and serum bactericidal activities) were studied. An association was found between the clinical course and the degree of nonspecific immunity suppression. The ozonized perfluorane was ascertained to have a more significant protective action on nonspecific immunity factors than perfluorane or the ozonized saline solution. The factors under study were significantly decreased when saline solution was administered, and with this there was a mass mortality of Series 4 rats on days 2—14 of the experiment. Conclusion. The therapeutic effect of the ozonized perfluorane is due to the activation of phagocytic mononuclear leukocytes and their increased count, to the antibacterial activity of ozone and the protective action on the nonspecific link of the body’s immunological resistance.